Doom patrol. The fourth and final season [videorecording (DVD)] - Guerrero, Diane, 1986-; Bowlby, April, 1980-; Bomer, Matthew, 1977-; Fraser, Brendan, 1968- (Warner Bros. Home Entertainment, 2024)
DC's unlikeliest group of heroes, the Doom Patrol, are ready to save the world... kind of. After suffering horrific accidents that gave them superhuman abilities, Cliff/Robotman, Larry/Negative Man, Rita/Elasti-Woman, Jane/Crazy Jane, and Vic/Cyborg, were each left scarred, disfigured, and ostracized, until mad scientist Dr. Niles Caulder brings the outcasts together to treat and protect them. Gritty and irreverent, Doom Patrol follows this part support group, part superhero team as they take on evil, otherworldly forces determined to destroy humankind, even if they want nothing to do with them.